Biologi Reproduksi Ikan Selais Terang Bulan (Kryptopterus bicirrhis, Valenciennes 1840) Di Desa Mentulik Sungai Kampar Kiri, Provinsi Riau - Nopiri, Ria; Elvyra, Roza (Universitas Jambi, 2018)
Study of biology reproductive selais Terang Bulan (Kryptopterus bicirrhis) fish in Mentulik village of Kampar Kiri River is conducted in February – July 2017. As for the goal of the research is to examine aspects of fish reproduction K. bicirrhis include sex ratio, development of the gonads, fecundity, spawning season and also spawning patterns. Fish K. bicirrhis totaled encounter 40-tail fish tail consists of 30 males and 10 females, fish tail with sex ratio of 3:1. Average total body length and weight Milter is the 8.2-11.5 cm (2.47-5,31 g) and females 8.4-11.5 cm (2.64-5,05 g), with a pattern of growth are allometrik negative. The level of maturity of the Gonads (WGP) males and females fish found in the WGP II-IV. Fecundity egg K. bicirrhis totaled 10,657 grain, and has a pattern of spawning are total spawner.